2019
DOI: 10.3390/e21030314
|View full text |Cite
|
Sign up to set email alerts
|

Development of Postural Stability Index to Distinguish Different Stability States

Abstract: A key factor for fall prevention involves understanding the pathophysiology of stability. This study proposes the postural stability index (PSI), which is a novel measure to quantify different stability states on healthy subjects. The results of the x-, y-, and z-axes of the acceleration signals were analyzed from 10 healthy young adults and 10 healthy older adults under three conditions as follows: Normal walking, walking with obstacles, and fall-like motions. The ensemble empirical mode decomposition (EEMD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Conversely, the subjects in the current study were all healthy young adults with high adaptability to changes in the environment [3]. The performance accuracy could be higher if the acceleration data in all axes were considered and the subjects were not only healthy young adults [21].…”
Section: Resultsmentioning
confidence: 85%
“…Conversely, the subjects in the current study were all healthy young adults with high adaptability to changes in the environment [3]. The performance accuracy could be higher if the acceleration data in all axes were considered and the subjects were not only healthy young adults [21].…”
Section: Resultsmentioning
confidence: 85%
“…This study only observed the performance based on the real events such as collisions and falls. In the previous studies, devices such as force platform (Nurwulan et al, 2015) and wearable accelerometers (Nurwulan et al, 2019a;Nurwulan et al, 2019b) was used to quantify the postural stability. By using wearable accelerometer, the stability of postural tasks such as standing and walking can be determined by calculating the postural stability index (Nurwulan et al, 2019a;Nurwulan et al, 2019b).…”
Section: Resultsmentioning
confidence: 99%
“…Postural stability index is derived from the entropy analysis of the acceleration data. It has been shown that entropy analysis can differentiate the subtle changes in the postural stability (Nurwulan et al, 2019a). The postural stability index would be very beneficial to evaluate the pedestrian safety in real environment.…”
Section: Resultsmentioning
confidence: 99%
“…Based on ensemble empirical mode decomposition (EEMD) and MSE and using an accelerometer, Nurwulan et al proposed a measure, the postural stability index (PSI), to distinguish different stability states in healthy subjects [ 13 ]. PSI is able to discriminate between normal walking and walking with obstacles in healthy subjects.…”
Section: Applications Of Existing Entropy-based Measuresmentioning
confidence: 99%